Management Of Deep Vein Thrombosis - Barnoyev Saidjon Sharifovich; Xayitov Dilshod Xayotovich (Genius Journals, 2023)
The term "deep vein thrombosis" (DVT) describes thrombosis that forms in the deep veins, usually in the lower limbs or pelvis. Due to the potentially lethal nature of pulmonary embolization, a consequence of DVT, this clinical condition has drawn attention. Consequently, in clinical practice, early detection and methodical management of DVT and associated consequences are crucial. In this review, we seek to provide an overview of recent research published within the last few years, given the recent improvements in clinical understanding of disorders related to deep vein thrombosis (DVT).
Keywords: Deep venous thrombosis; homeostasis; antithrombotic therapy